Comparative Evaluation of Profiles of Antibodies to Mycobacterial Capsular Polysaccharides in Tuberculosis Patients and Controls Stratified by HIV Status - Yu, Xian (American Society for Microbiology, 2012)
Despite the complexity of tuberculosis (TB) serology, antibodies (Abs) remain attractive biomarkers for TB. Recent evidence of a mycobacterial capsule that consists mainly of the polysaccharides arabinomannan (AM) and glucan provides new options for serologic targets. For this study, Ab responses to AM and glucan for 47 U.S. TB patients (33 HIV negative [HIV(−)], 14 HIV positive [HIV(+)]), 42 healthy controls, and 38 asymptomatic HIV(+) controls were evaluated by enzyme-linked immunosorbent assays (ELISAs). The results were compared with Ab responses to the mycobacterial glycolipid cell wall antigen lipoarabinomannan (LAM) and to the proteins malate synthase (MS) and MPT51. We found that the main immunoglobulin (Ig) isotype response to polysaccharides was IgG, predominantly of subclass IgG2. IgG responses to AM were significantly higher for HIV(−) and HIV(+) TB cases than for controls (P, <0.0001 and <0.01, respectively); significantly higher for HIV(−) than for HIV(+) TB cases (P, <0.01); and significantly higher in sputum smear-positive than smear-negative patients in both HIV(−) and HIV(+) cases (P, 0.01 and 0.02, respectively). In both TB groups, titers of Ab to glucan were significantly lower than titers of Ab to AM (P, <0.0001). IgG responses to AM and MS or to AM and MPT51 did not correlate with each other in HIV(−) TB patients, while they correlated significantly in HIV(+) TB patients (P, 0.01 and 0.05, respectively). We conclude that Ab responses to AM could contribute to the serodiagnosis of TB, especially for HIV(−) TB patients. This study also provides new and important insights into the differences in the profiles of Abs to mycobacterial antigens between HIV(−) and HIV(+) TB patients.